Unravelling the structure of glycosyl cations via cold-ion infrared spectroscopy - Eike Mucha (Nature Portfolio, 2018)
Glycosyl cations are key intermediates in glycosylation reactions, but their structure has remained elusive due to their transient nature. Here, the authors perform an in-depth structural analysis and report that C2-participating protective groups induce acetoxonium cations with distinct ring conformations.